Experiences of Iranian Patients with Thalassemia Major Regarding Their Palliative and Supportive Care Needs: A Qualitative Content Analysis - Mehrnaz Ahmadi; Maryam Rassouli; Mahin Gheibizadeh; Abbas Ebadi; Marziyeh Asadizaker (International Journal of Community Based Nursing and Midwifery)
Background: Due to the long-term and progressive nature of β-thalassemia major (β-TM), patientsneed comprehensive palliative and supportive care covering physical, mental, social, and spiritualaspects. The first step in providing palliative and supportive care is identifying the patients’ needs.This study aimed to explore the palliative and supportive care needs of patients with β-TM.Methods: A qualitative study was conducted from April 2019 to December 2019. The study involvedin-depth semi-structured individual interviews with 20 individuals living with β-TM at a universityhospital in Ahvaz, Iran. The participants were selected through purposive sampling. Interviewscontinued until the saturation of data. All interviews were recorded, transcribed, and analyzed withconventional content analysis following the steps recommended by Elo and Kyngäs using MAXQDAsoftware version 10.Results: Five overarching categories, each with multiple subcategories, were identified: “physicalhealth needs,” “sexual and reproductive health needs,” “mental and emotional health needs,” “socialneeds,” and “need for access to comprehensive health services.”Conclusion: According to the results of this study, unmet needs are prevalent throughout the thalassemiajourney. Patients with β-TM require individual, psychosocial, and comprehensive healthcare supportto address their needs. Therefore, further research is necessary to develop a nursing care plan for β-TMpatients focusing on supportive-palliative care needs.